EU ideology. Issue 1 (2nd January 2016) - Petrović, Nikola
Abstract : The idea of Europe was radically transformed after the accomplishment of the idea of European unification. The European Union (EU) and Europe at the beginning of the twenty-first century were defined by a broad common ideology that consists of ideologies such as antinationalism, social democracy, pacificism and environmentalism. These ideologies are presented by pro-EU scholars and politicians as ideologies rooted in European history and parts of European identity and as being mostly absent in the American policies. The emergence of EU ideology is traced in the relaunch of European integration in the mid-1980s and in Delors' conflict with Thatcher. It is argued that the emergence of EU ideology is the result of two long-term historical developments: the deepening and enlargement of European integration; and the changing relations between the USA and Europe. It is concluded that the emergence of EU ideology resembles the emergence of nationalism and national ideologies.